The Implementation of Card Sort Active Learning with Mind Mapping to Increase Students’ Learning Interest in Biology at the Students’ of VII-E SMP Negeri 5 Surakarta - Ninik Ambarini; Alvi Rosyidi; Joko Ariyanto (BIO-PEDAGOGI, 2013)
The  purpose of this research is to improve students’ learning interest in biological  study  by  applying  of active  learning  Card Sort  accompanied Mind Mapping strategy at the students of 5 Junior High School in class VII-E. This research was a classroom action research which the research design consist  of two  cycles.  Each  cycle  consisted of four  basic  steps, they  were planning, action, observation,  and  reflection. The  data  were  collected by  using questionnaire, observation, and interview  methods. The  data  collected were arranged in the form of table and graph and then were analysed. The technics of analysing data that used in this research was qualitative analysis. The qualitative analysis described the data resulted from questionnaire, observation and interview during the action research. The  conclusion  of  research obtained  that  the  application  of  active learning  Card Sort  accompanied Mind Mapping  can improve  students’  learning interest in biological study. This matter seen from result of research proved that improvement each indicator of  learn  interest  in biological study  have  earned to reach goals which have been determined that was 75%. Result of mean percentage of learn interest questionnaire pre-cycle was 68,64%, and last cycle was 76,71%. While result of mean percentage of learn interest observation pre-cycle was 30%, and last  cycle  was  81,67%. Research discontinued at  second  cycle  considering goals have been reached. Key Words: Card Sort, Mind Mapping, Learning Interest